King Rother - Lichtenstein, Robert (University of North Carolina studies in the Germanic languages and literatures, 2020)
Originally published in 1962, Robert Lichtenstein's translation of King Rother made the medieval epic available to English-speaking audiences for the first time. His translation in rhymed couplets seeks to convey the humorous spirit of the original and an introduction places the poem in its historical context.